2014
DOI: 10.1159/000362616
|View full text |Cite
|
Sign up to set email alerts
|

Online Survey of Cancer Patients on Complementary and Alternative Medicine

Abstract: Introduction: Complementary and alternative medicine (CAM) is often used by cancer patients, yet, communication with the oncologist is poor. The objective of our study was to gather information on patients' usage of CAM, source of information, and aims, in order to derive strategies to improve the communication between physicians and patients on this topic. Materials and Methods: An online survey was conducted by linking a standardized questionnaire to the largest internet portal for cancer patients in Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 28 publications
7
58
2
10
Order By: Relevance
“…Die Beweggründe für oder gegen eine Inanspruchnahme der Misteltherapie ließen sich den übergeordneten Kategorien «Wahrgenommene Indikation» und «Abwägungen bei der Entscheidungsfindung» zuordnen. Der Prozentsatz an Anwendern in unserer Studie entspricht der aktuellsten Studie zur Nutzung von KM durch Krebspatienten in Deutschland [12]. …”
Section: Diskussion Und Schlussfolgerungenunclassified
See 2 more Smart Citations
“…Die Beweggründe für oder gegen eine Inanspruchnahme der Misteltherapie ließen sich den übergeordneten Kategorien «Wahrgenommene Indikation» und «Abwägungen bei der Entscheidungsfindung» zuordnen. Der Prozentsatz an Anwendern in unserer Studie entspricht der aktuellsten Studie zur Nutzung von KM durch Krebspatienten in Deutschland [12]. …”
Section: Diskussion Und Schlussfolgerungenunclassified
“…Auch in einer Studie von 1998, die die Inanspruchnahme von KM bei Krebspatienten, deren Motivation für die Inanspruchnahme und Erwartungen an die KM untersuchte, war die Misteltherapie mit 61,6% das meistverwendete KM-Verfahren [7]. Anscheinend hat jedoch der Anteil an Patienten, die zur Misteltherapie greifen, im zeitlichen Verlauf stark abgenommen [8,9,10,11,12]. In einer Online-Befragung von 2011, die damit die aktuellste Erhebung der Inanspruchnahme von KM in Deutschland darstellt, nutzten nur etwa 15% der 80 befragten Brustkrebs-Patientinnen [11] bzw.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A meta-analysis indicated an increase in TCAM use for patients with cancer from an estimated 25% in the 1970s and 1980s to more than 32% in the 1990s and to 49% after 2000 (6). Data from recent studies have indicated that the rate of TCAM use is 77% or even higher (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no standard in the literature outlining the procedure for integrative medicine consultations or the instruments required for such consultations. There are many questionnaires out there, but they are mostly survey questionnaires which aim to assess the incidence, reasons for, methods and general use of CAM by patients or to evaluate existing structures and the acceptance and attitude towards CAM of physicians and medical practitioners [21,52]. Prior to our study there was no published questionnaire which could be used as a standard instrument to record the current status in integrative medicine consultations and serve as a decision-making tool for CAM therapies.…”
mentioning
confidence: 99%